Pelvic floor muscle rehabilitation for patients with lifelong premature ejaculation: a novel therapeutic approach. (June 2014) - Pastore, Antonio L.; Palleschi, Giovanni; Fuschi, Andrea; Maggioni, Cristina; Rago, Rocco; Zucchi, Alessandro; Costantini, Elisabetta; Carbone, Antonio
Objectives: Premature ejaculation is the most common male sexual disorder. The aim of the study was to evaluate the possible therapeutic role of pelvic floor muscle rehabilitation in patients affected by lifelong premature ejaculation. Methods: We treated 40 men with lifelong premature ejaculation, reporting, a baseline intravaginal ejaculatory latency time (IELT) ≤ 1 min, with 12-week pelvic floor muscle rehabilitation. Results: At the end of the rehabilitation, mean IELTs were calculated to evaluate the effectiveness of the therapy. At the end of the treatment, 33 (82.5%) of the 40 patients gained control of their ejaculatory reflex, with a mean IELT of 146.2 s (range: 123.6–152.4 s). A total of 13 out of 33 (39%) patients were evaluated at 6 months follow up, and they maintained a significant IELT (112.6 s) compared with their initial IELT (mean 39.8 s). Conclusions: The results obtained in our subjects treated with pelvic floor rehabilitation are promising. This therapy represents an important cost reduction compared with the standard treatment (selective serotonin reuptake inhibitors). Based on the present data, we propose pelvic floor muscle rehabilitation as a new, viable therapeutic option for the treatment of premature ejaculation.